Intense interface seismicity triggered by a shallow slow slip event in the Central Ecuador subduction zone. Issue 6 (17th June 2013) - Vallée, Martin; Nocquet, Jean‐Mathieu; Battaglia, Jean; Font, Yvonne; Segovia, Monica; Régnier, Marc; Mothes, Patricia; Jarrin, Paul; Cisneros, David; Vaca, Sandro; Yepes, Hugo; Martin, Xavier; et al.
Abstract: [1] We document a 1 week long slow slip event (SSE) with an equivalent moment magnitude of 6.0–6.3 which occurred in August 2010 below La Plata Island (Ecuador), south of the rupture area of the 1906 Mw = 8.8 megathrust earthquake. GPS data reveal that the SSE occurred at a depth of about 10 km, within the downdip part of a shallow (<15 km), isolated, locked patch along the subduction interface. The availability of both broadband seismometer and continuous geodetic station located at the La Plata Island, 10 km above the SSE, enables a careful analysis of the relationships between slow and rapid processes of stress release along the subduction interface. During the slow slip sequence, the seismic data show a sharp increase of the local seismicity, with more than 650 earthquakes detected, among which 50 have a moment magnitude between 1.8 and 4.1. However, the cumulative moment released through earthquakes accounts, at most, for 0.2% of the total moment release estimated from GPS displacements. Most of the largest earthquakes are located along or very close to the subduction interface with focal mechanism consistent with the relative plate motion. While the earthquake sizes show a classical distribution (Gutenberg‐Richter law with a b‐value close to 1), the space‐time occurrence presents a specific pattern. First, the largest earthquakes appear to occur randomly during the slow slip sequence, which further evidence that the seismicity is driven by the stress fluctuations related to aseismic slip. Moreover, the seismicity observed during the SSE consists in individual events and families of repeating earthquakes. These observations indicate that the stress increment induced by the episodic aseismic slip may lead both to sudden seismic moment release and to progressive rupture within small locked patches. This study offers an a posteriori interpretation of the seismogenesis in the Central Ecuador subduction zone, where intense seismic swarms have been regularly observed (1977, 1998, 2002, and 2005). These swarms have likely been triggered by large‐magnitude slow slip events. Key Points: This study documents how slow slip and seismicity can be intimately related Microseismicity is driven by slow slip and often organized in specific families Hypothesis of slow slip‐induced seismicity is supported by direct observation